2016
DOI: 10.1097/mao.0000000000001081
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Spontaneous Recovery of Tinnitus Related to Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Objective:To evaluate the characteristics and spontaneous recovery of tinnitus related to idiopathic sudden sensorineural hearing loss (ISSNHL).Study Design:Retrospective analysis from two randomized placebo-controlled clinical trials for treatment of ISSNHL within 48 hours from onset (Study A), or of tinnitus related to ISSNHL within 3 months from onset (Study B).Setting:Forty-eight European sites (academic tertiary referral centers, private ENT practices).Patients:One hundred thirteen adult patients of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
6
43
0
Order By: Relevance
“…Finally, a significant positive correlation was found between mean AT and THI as well as negative correlations between mean AT and mean SDS and between mean SDS and THI (Table 1). This confirms the association between loss of auditory input, tinnitus onset and speech discrimination impairment in the acute phase of the disease (Muhlmeier et al, 2016).…”
Section: Correlation Analysissupporting
confidence: 83%
“…Finally, a significant positive correlation was found between mean AT and THI as well as negative correlations between mean AT and mean SDS and between mean SDS and THI (Table 1). This confirms the association between loss of auditory input, tinnitus onset and speech discrimination impairment in the acute phase of the disease (Muhlmeier et al, 2016).…”
Section: Correlation Analysissupporting
confidence: 83%
“…There exists a multitude of cross-sectional studies on factors associated with chronic tinnitus (e.g., this Frontiers Topic), whereas only few studies have attempted to assess participants with acute tinnitus ( 5 7 ) including a study that investigated tinnitus patients one year after their first visit to a clinic if they entered the clinic within 6 months of tinnitus onset ( 8 ). Therefore, time course as well as mechanisms involved in the transition from the acute to the chronic condition are unknown, and factors predisposing for the development of a chronic, disabling, or decompensated tinnitus are mostly inferred from retrospective reports.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, time course as well as mechanisms involved in the transition from the acute to the chronic condition are unknown, and factors predisposing for the development of a chronic, disabling, or decompensated tinnitus are mostly inferred from retrospective reports. Furthermore, studies on acute tinnitus usually were concerned with tinnitus following sudden HL ( 6 , 7 ) or acute acoustic trauma ( 9 ), which appear to be distinct as indicated by high remission rates which may reach 70% ( 10 ). High remission rates concomitant with an incidence of HL are likely related to partial recovery of hearing function in the first weeks after a temporary threshold shift ( 11 ), but not all patients can relate tinnitus onset to worsening of their hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the symptom of tinnitus decreased from 70% to 30% after 7 to 10 days SCT. In IT steroid procedure the improvement is much higher, ranging from 75% to 100% (Choi et al 2013;Hyun 2016;Mühlmeier et al 2016). In the current study, in terms of tinnitus, there was a significant improvement in 7 out of 8 patients.…”
Section: Discussionmentioning
confidence: 98%